Improved Methods of Blasting Concrete for Welland Canal Rehabilitation - Craig Copping; Ray Jambakhsh (International Society of Explosives Engineers, 1994)
The St. Lawrence Seaway's Welland Canal has been undergoing a rehabilitation program that requires the removal of deteriorated concrete from the 25 meter high lock walls. Multi million dollar contracts must be completed during the three month winter freeze up. New blast designs have drastically cut the time required for concrete demolition. All blast results including vibration, noise, underbreak, overbreak, scaling and flyrock have been improved and at a lower cost.